2019
DOI: 10.1038/s41598-019-39073-w
|View full text |Cite
|
Sign up to set email alerts
|

SerpinB2 is involved in cellular response upon UV irradiation

Abstract: Ultraviolet light induced pyrimidine dimer is a helix distortion DNA damage type, which recruits repair complexes. However, proteins of these complexes that take part in both DNA damage recognition and repair have been well-described, the regulation of the downstream steps of nucleotide excision repair (NER) have not been clearly clarified yet. In a high-throughput screen, we identified SerpinB2 (SPB2) as one of the most dramatically upregulated gene in keratinocytes following UV irradiation. We found that bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Our results and recent studies also showed that UV irradiation induces robust gene expression changes in the Hker E6SFM keratinocyte cell line [19][20][21][22]. Among the upregulated genes, we identified several members of the B clade of the Serpin superfamily, including SerpinB2, SerpinB10, and SerpinB13 [19].…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results and recent studies also showed that UV irradiation induces robust gene expression changes in the Hker E6SFM keratinocyte cell line [19][20][21][22]. Among the upregulated genes, we identified several members of the B clade of the Serpin superfamily, including SerpinB2, SerpinB10, and SerpinB13 [19].…”
Section: Introductionsupporting
confidence: 82%
“…In this study, we investigated a novel, yet-to-be-characterized function of the SPB10 protein following UV irradiation. Our preliminary microarray data indicated that members of the SerpinB family could play a role in UV-induced cellular responses [19,20]. We revealed an increase in the mRNA level of SPB10 upon UV irradiation in three skinderived cell lines (Hker E6SFM, HaCaT, and A375).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…UVA (315–400 nm) mainly induces oxidative stress and DNA damage via reactive oxygen species (ROS) generation; UVB exposure (280–315 nm) mostly causes direct DNA damage through the production of intra-strand DNA base cross-linking, including cyclobutane pyrimidine dimers (CPDs) and (6–4) pyrimidine-pyrimidone photoproducts (6–4)PPs] and their Dewar isomers [ 19 ]. In humans, UVB-induced photoproducts are repaired by the evolutionary conserved but slow nucleotide excision repair (NER) mechanism [ [20] , [21] , [22] ]. UV irradiation can reach the surface of an organism.…”
Section: Introductionmentioning
confidence: 99%
“…In response to UV irradiation, the precise function of these factors ensures the preservation of genome integrity in a coordinated spatiotemporal manner, thereby significantly contributing to the prevention of cancerous malformations. We have already shown that SerpinB2 can play a role in the regulation of the NER pathway through the XPB protein as well as the ubiquitin network, and this function is altered in tumor cells [98]. Hence, being aware of any malfunction of even one of these factors can contribute to the better understanding the molecular background of the tumor.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%